RADIOGRAPHIC CHANGES IN THE BONE GRAFTS DURING GUIDED BONE REGENERATION WITH THE USE OF TITANIUM MESH ON CLASSICAL AND AUTHORS' OWN METHODS FOR THE MUCOSAL FLAPS DETACHMENT - Kaplun, D.V.; Avetikov, D.S.; Ivanytska, O.S.; Boiko, I.V.; Havryliev, V.M. (World of Medicine and Biology, 2020)
One of the major problems in rehabilitation of bone volume loss in preparing patients for dental implantation is the bone graft exposure and its infection in the result of ischemic processes in the mucousal flap that covers it. We performed 27 surgical interventions for guided bone regeneration using titanium mesh according to the classical method of detachment of trapezoidal mucousal flap and 30 surgical interventions on authors' own method of detachment and mobilization of the mucousal flap. The augmentation was performed in the mandibular distal segments. Our studies have shown that the optimization of the limits of detachment and mobilization of mucousal and mucoperiosteal flaps, compared with the classical method of trapezoidal flaps, leads to a decrease in bone graft volume loss by 1.9%. The data indicate the possibility of improving the flap surgery efficiency during bone augmentation in patients with acquired edentulism.
Keywords: dental augmentation; CBCT; mucosal flaps